Innovative approaches and digitalization in managing insurance claims - Iskandarov Abdurasul Mirjalil oglu (THE INNOVATION ECONOMY, 2026)
This article analyzes innovative approaches and digitalization processes in the management of insurance claims. It highlights the importance of artificial intelligence, blockchain, Big Data, and online platforms in ensuring efficiency, transparency, and promptness of claim settlements. Furthermore, current measures and prospective directions of digitalizing insurance claims in Uzbekistan are examined